2021
DOI: 10.1097/gox.0000000000003533
|View full text |Cite|
|
Sign up to set email alerts
|

Application of FACE-Q and NOSE in Nasal Reconstruction with Paramedian Frontal Flap after Skin Cancer Resection

Abstract: Introduction: Nonmelanoma skin cancer (NMSC) is responsible for high morbidity and mortality, resulting in a high cost to the health system. The nose is the leading region affected by this type of tumor and may need reconstruction by tissue transfer. The paramedian forehead flap (PFF) is one of the main options used, and the factors that influence the result should be studied. The FACE-Q questionnaire allows the assessment of appearance, quality of life, and side effects related to the procedure, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Pagotto et al demonstrated a statistically significant relationship between time to completion of reconstruction and quality of life of patients undergoing nasal reconstruction with PMFF. Patients who completed the reconstruction in a period of less than six months had better results in the quality-of-life domain of the FACE-Q questionnaire compared with the others (p=0.002) 27 . In our sample, the median time to completion of the reconstruction was six months (IQR 3-24).…”
Section: Discussionmentioning
confidence: 93%
“…Pagotto et al demonstrated a statistically significant relationship between time to completion of reconstruction and quality of life of patients undergoing nasal reconstruction with PMFF. Patients who completed the reconstruction in a period of less than six months had better results in the quality-of-life domain of the FACE-Q questionnaire compared with the others (p=0.002) 27 . In our sample, the median time to completion of the reconstruction was six months (IQR 3-24).…”
Section: Discussionmentioning
confidence: 93%
“…2 We included fifteen patients who underwent nose reconstruction with free flaps over the course of four years to complete the FACE-Q questionnaire so that we were able evaluate their level of self-satisfaction with both their aesthetic and functional appearance. 9,10 After that, a tabulation and analysis of the results was performed (Table 1). Positive findings were discovered in nine of the patients who had completed the FACE-Q questionnaire.…”
Section: Discussionmentioning
confidence: 99%